Psychological Safety, Trading Performance, and Legal Certainty Among Students Engaged in XAU/USD Trading - Yuarini Wahyu Pertiwi; Endang Hadrian; Raihan Saputra (Journal of Islamic Psychology and Behavioral Sciences, 2026)
A growing number of high school and university students are learning XAU/USD trading through nonformal education channels, despite frequent margin calls and ongoing legal uncertainty surrounding trading platforms and brokers. This study examines two independent propositions: a psychological proposition on the relationship between Psychological Safety and Trading Performance, and a legal proposition on legal certainty for student XAU/USD trading. The psychological analysis involved 200 student traders and employed correlation, regression, and group comparison analyses using JASP, while the legal analysis adopted normative statutory and conceptual approaches. Results showed that Psychological Safety was positively associated with Trading Performance (r = .576, p < .001) and significantly predicted performance, explaining 33.1% of its variance (R² = .331). Trading Performance differed significantly according to trading experience and capital size, but not by gender or education level, whereas Psychological Safety showed no significant group differences. The legal analysis found that legal certainty remains incomplete due to the ongoing transfer of supervisory authority from Bappebti to OJK and Bank Indonesia, limited protection for clients of foreign futures brokers, the widespread use of unlicensed platforms, and concerns regarding underage student traders. These findings suggest that strengthening Psychological Safety and improving regulatory certainty are complementary priorities for reducing vulnerabilities among student XAU/USD traders.